Aliasing of 60-Hz Artifact as a Result of Compressed Time Base. Issue 5 (September 2017) - Bolen, Robert D.; Edwards, Jonathan C.; Halford, Jonathan J.
Abstract : Purpose: Digital EEG has brought about greater flexibility in data interpretation but has also resulted in new and unique artifacts. As digital EEG has evolved, an increase in intensive care unit monitoring has occurred, bringing more sources of artifact to light. Aliasing as a result of a combination of compressed time base and display monitor resolution can result in appearance of spurious waveforms that can potentially skew interpretation. Methods: A portion of a digital EEG from an intensive care unit patient acquired at a sample rate of 1, 024 Hz was reviewed at a time base of 15 mm/second on a monitor with a resolution of 1, 920 × 1, 080. Results: At a time base of 15 mm/second, a 60-Hz artifact resulted in the appearance of a 4-Hz delta artifact that resolved when the time base was changed to a more standard 30 mm/second. Conclusions: A software malfunction of the digital antialiasing filter for display resulted in the appearance of a novel 4-Hz artifact.